Investment Awareness and Behavioral Perception towards Selection of Investment Avenues among Teaching Professionals in Andhra Pradesh State - Madanu, Bala Swamy; Nagaraj, K V (Journal of Business Management, 2024)
Teachers can save well and invest wisely to have a fantastic retirement plan, even though they work in a noble profession with modest pay. This blog will cover risk management strategies, investment plans, and the moral and social obligations associated with investing. If you are a teacher intending to begin your investment adventure, have recently begun your teaching career, or an experienced teacher wanting to begin an investment, this guide will assist you in investing your hard-earned money effectively to get decent returns. The goal of this study is to comprehend how teaching professionals save, invest, and make their choices. The characteristics of investment planning, factors influencing investment preferences, the mindset of teaching professionals when choosing an investment avenue, and their desire for their savings to be invested in the safest and most liquid manner are just a few of the many facets of savings and investment behavior and selection. However, each person's choice differs based on their tolerance for risk. Their investment objectives likewise vary, ranging from financial stability to supplementary income. This research seeks to identify the reasons responsible for increased investment activity among young professionals. The current study investigated the investing behavior of teaching profession investors using a structured survey, and this study examines the behavioral aspects impacting investment among teaching professionals.